COMMUNICATIVE LANGUAGE TEACHING: IMPLICATIONS FOR THE COMMUNICATIVE CLASSROOM - Farid, Achmad (Educate, 2015)
A linguistically informed teacher about views of language can either adopt structuralist or functionalist approach to successfully teach language in his/her classroom. The Communicative Language Teaching is aimed at attracting second language learners to purposeful classroom activities in which learners use and reproduce language as it is practiced in real communication beyond the classroom in meaningful situations. To achieve this, a linguistically well-informed language teacher needs to focus on his role as a facilitator, an interdependent member of the classroom, a needs analyst, a counsellor, and a group activity manager. In addition, the teacher needs to remember that in communicative classroom students negotiate (for meaning) between themselves in their own ways in the classroom communications. Therefore, a linguistically well-informed teacher needs to consider what classroom activities he needs to pick up to achieve the ultimate goal of the CLT, which is the communicative competence.